Influence of heat (thermic) treatments of tempering and normalization on the microstructure, hardness, and mechanical resistance to corrosion of highly resistance brass - Rosario Francia, Samuel (2010)
The high resistance brass belongs to the copper-zinc alloys, which contains elements such as iron, aluminum, manganese and nickel, other elements in very small percentage in such a way that they do not affect the acquired properties and in which manganese increases the solubility of iron, improving mechanical properties and, along with nickel, its resistance to corrosion. The presence of aluminum and iron allow them to be heat treated, the objective of this work is to establish the conditions of heat treatment and its influence on physical, mechanical and corrosion properties.